Pediatric Informatics Computer Applications in Child Health - Lehmann, Christoph U.; Kim, George R.; Johnson, Kevin B. (Health Informatics, 2009)
Now is a critical time in pediatric informatics. As information technologieselectronic health records (EHRs), personal health records (PHRs), computerized physician order entry (CPOE)and standards (HL7) are developed to improve the quality of health care, it is imperative for policy makers and pediatricians to be aware of their impact on pediatric care and child health. Informed child advocates must be at the planning table as national and regional health information networks are developed to insure the unique health care needs of children are being met. Pediatric Informatics: Computer Applications in Child Health is a current digest of the important trends in pediatric informatics, written by leading experts in the field. This book explores how the management of biomedical data, information, and knowledge can optimize and advance child health. The contributors investigate the specific importance of pediatric informatics is derived from the biological, psychological, social and cultural needs that the distinguish children from other populations. These distinctions create complexities in the management of pediatric data and information that make children a vulnerable population and require the development of a new body of knowledge in pediatric informatics.